Variations of salivary concentration of cytokines and chemokines in presence of oral squamous cell carcinoma. A case-crossover longitudinal prospective study. (August 2019) - Val, Matteo; Sidoti Pinto, Girolamo Antonio; Manini, Lorenzo; Gandolfo, Sergio; Pentenero, Monica
Highlights: Squamous cell carcinoma accounts for over 90% of all head-neck cancers. Salivary biomarkers allow simple, non-invasive, stress-free sampling. Salivary concentration of different cytokines are potential biomarker for OSCC. Salivary concentration of IL-1β, IL-6, IL-8, VEGF was increased in the presence of OSCC. Abstract: Salivary biomarkers represent a promising diagnostic tool. Non-invasive and stress-free sampling results in objective parameters able to overcome the need of clinical expertise required for a correct interpretation of early oral squamous cell carcinoma (OSCC). The present study aims at evaluating potential variations in the salivary concentration of cytokines in presence of OSCC. Twenty patients who underwent surgical resection of OSCC were enrolled in order to assess the variation of the salivary concentration of cytokines and chemokines in a longitudinal prospective case-crossover setting. The salivary concentration of 27 salivary cytokines/chemokines was assessed before and after surgical resection of OSCC. In cases of relapsing/recurrent disease further assessments were performed. In presence of OSCC an increased concentration of IL-8(p = 0.004), IL-6(p = 0.005), VEGF(p = 0.014), MIP-1ß(p = 0.033), IP-10(p = 0.047), IL-1β(p = 0.049) was observed; conversely the concentration of IFN-γ(p = 0.036) and IL-5(P = 0.048) decreased. In cases with relapsing/recurrent disease IL-5, IL-6 and MIP-1β showed variations consistent with the previously reported results. Further studies are needed in order to confirm these results and to determine reference values to determine the presence or absence of disease.